2016
DOI: 10.1111/adb.12427
|View full text |Cite
|
Sign up to set email alerts
|

Reward and relief dimensions of temptation to drink: construct validity and role in predicting differential benefit from acamprosate and naltrexone

Abstract: Researchers have sought to distinguish between individuals whose alcohol use disorder (AUD) is maintained by drinking to relieve negative affect (“relief drinkers”) and those whose AUD is maintained by the rewarding effects of alcohol (“reward drinkers”). As an opioid receptor antagonist, naltrexone may be particularly effective for reward drinkers. Acamprosate, which has been shown to down-regulate the glutamatergic system, may be particularly effective for relief drinkers. This study sought to replicate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 56 publications
4
62
1
1
Order By: Relevance
“…These results provide initial evidence that demographical and clinical differences between treatment-seekers and non-treatment seekers with AUD are significantly related to treatment outcomes. And while in-depth analyses of moderators of response to each intervention in the COMBINE Study (i.e., Acamprosate, Naltrexone, and CBI) are beyond the scope of the present study, recent studies have proposed a host of putative moderators, including craving for alcohol [21], reward and relief drinking dimensions [22], social network [23], and body mass index (BMI) [24]. In the context of this study, we sought to examine the clinical significance (i.e., prediction of clinical outcome) of the variables found to differ between treatment-seekers and non-treatment seekers, as opposed to investigate their potential moderating role.…”
Section: Discussionmentioning
confidence: 99%
“…These results provide initial evidence that demographical and clinical differences between treatment-seekers and non-treatment seekers with AUD are significantly related to treatment outcomes. And while in-depth analyses of moderators of response to each intervention in the COMBINE Study (i.e., Acamprosate, Naltrexone, and CBI) are beyond the scope of the present study, recent studies have proposed a host of putative moderators, including craving for alcohol [21], reward and relief drinking dimensions [22], social network [23], and body mass index (BMI) [24]. In the context of this study, we sought to examine the clinical significance (i.e., prediction of clinical outcome) of the variables found to differ between treatment-seekers and non-treatment seekers, as opposed to investigate their potential moderating role.…”
Section: Discussionmentioning
confidence: 99%
“…We have found preliminary support for this notion in our secondary analysis of Project MATCH. We demonstrated that the frequency of using coping skills at post-treatment significantly mediated the treatment effects of CBT for alcohol use disorder among outpatient clients with high dependence severity, but not those with low dependence severity (Roos, Maisto, & Witkiewitz, in press). …”
Section: A Contextual Model Of Self-regulation Change Mechanismsmentioning
confidence: 92%
“…However, they did not report whether coping skills mediated the effects of TES on longer-term outcomes. Finally, Roos, Maisto, and Witkiewitz (in press) conducted secondary analyses of the Project MATCH data to examine whether baseline alcohol dependence severity moderated the indirect effect of CBT on alcohol use outcomes via coping skills. Results indicated that end-of-treatment coping skills mediated the positive treatment effects of CBT on one-year drinking outcomes among outpatient clients with high dependence severity, but not those with low dependence severity.…”
Section: Extant Research On Self-regulation As a Mobc In Behavioral Amentioning
confidence: 99%
See 1 more Smart Citation
“…Those with greater substance use and negative affect severity are more likely to benefit from mindfulness-based relapse prevention (Roos et al, 2017a). Furthermore, reasons for alcohol use (e.g., reward vs. relief motives, drinking to cope) differentially predict response to naltrexone and acamprosate (Mann et al, 2018;Roos et al, 2017b;Witkiewitz et al, 2019b) and cognitive-behavioral therapy (Anker et al, 2016).…”
mentioning
confidence: 99%